Annealing Temperature Effects on the Thermoluminescence Glow Curve and Kinetic Parameters of the Natural Soil Salt Phosphor from Zuwara Sabkhas in Northwestern Libya, as Radiation Dosimetry - Fawzeia Khamis; Diaa El-Dean Arafah (AlQalam Journal of Medical and Applied Sciences, 2025)
In this work, the thermoluminescence (TL) properties and kinetic parameters of soil salts that collect on the soil surface after rainfall are studied. The samples were crushed and pressed carefully to form circular disc pellets before being irradiated with a calibrated 90Sr-90Y source-β-particles emission source 1Gy. The optimum annealing condition was determined by varying the annealing temperature from room temperature (RT) up to 700oC/1h. TL responses exhibited two peaks at about 175°C and 235°C in the glow curve. By increasing the annealing temperature, we observed that the glow curve has a single sharp peak at about 225 °C and a broad shoulder at high temperature. The phase crystalline structure of the soil salt was analyzed by the powder X-ray diffraction technique. These phosphors exhibited a high sensitivity, which might prove useful for TL dosimetry in applications.